2022
DOI: 10.3390/ijms23010484
|View full text |Cite
|
Sign up to set email alerts
|

Niclosamide Suppresses Migration and Invasion of Human Osteosarcoma Cells by Repressing TGFBI Expression via the ERK Signaling Pathway

Abstract: Osteosarcoma is a highly common malignant bone tumor. Its highly metastatic properties are the leading cause of mortality for cancer. Niclosamide, a salicylanilide derivative, is an oral antihelminthic drug of known anticancer potential. However, the effect of niclosamide on osteosarcoma cell migration, invasion and the mechanisms underlying have not been fully clarified. Therefore, this study investigated niclosamide’s underlying pathways and antimetastatic effects on osteosarcoma. In this study, U2OS and HOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Using the analysis approach, we identified several proteins with differential expression between M19 and ES36. All these proteins are of particular interest since their roles in promoting metastases [ 25 , 26 ] and sarcoma progression [ 27 , 28 ] have been demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…Using the analysis approach, we identified several proteins with differential expression between M19 and ES36. All these proteins are of particular interest since their roles in promoting metastases [ 25 , 26 ] and sarcoma progression [ 27 , 28 ] have been demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…Niclosamide is an attractive candidate as it is already available for clinical use to treat parasitic infections in millions of people worldwide. It has been shown to be active in osteosarcoma cell lines, U2OS, HOS and MG63, and, furthermore, to prevent metastatic spread in the lungs in a mouse model of osteosarcoma ( Li et al, 2015 ; Reddy et al, 2020 ; Yeh et al, 2022 ). The effect of niclosamide on osteosarcoma cells resistant to chemotherapy, a most relevant issue, had not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt/β-catenin, ATF3, PERK, eIF4E, NK-ĸB, STAT3, and mTOR have been reported to be involved in niclosamide’s action in cancer cells ( Arend et al , 2016 ; Liu Z et al, 2016 ; Weng et al, 2016 ; Wang et al , 2019 ; Wei et al , 2021 ). Several studies also highlight the inhibitory effects of niclosamide on osteosarcoma cells and xenograft mouse model ( Li et al , 2015 ; Reddy et al, 2020 ; Yi et al, 2021 ; Yeh et al, 2022 ). However, it is not known whether niclosamide is effective against chemo-resistant osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that DCA inhibits migration ( Florio et al, 2018 ; Tataranni et al, 2019 ; Guo et al, 2022a ) of cells as well as invasion ( Guo et al, 2022a ). Nic has been shown to have anti-migratory and anti-invasive properties ( Zhu et al, 2019 ; Guo et al, 2022b ; Yeh et al, 2022 ). In this study, DCA inhibited migration in H226 cells while Nic suppressed migration in 3 MPM cells lines.…”
Section: Discussionmentioning
confidence: 99%